Match-related technical performance of high-level technical judo athletes during the 2016-2020 Olympic Games: an analysis by phase and weight category - Moronta, D.; Ojeda-Aravena, A.; Dopico-Calvo, X.; Kons, R.; Calvo-Rico, B.; García-García, J. M. (International Journal of Performance Analysis in Sport, 2025)
To examine the relationship between combat outcomes (Wazari vs. Ippon) and the techniques used in the Olympic Games Rio 2016 and Tokyo 2020, an observational and retrospective analysis was conducted on the weight categories and rounds of male and female judo athletes. Two judo experts (Black Belts with 20 years of experience) independently coded the techniques. Chi-square tests, odds ratios (OR), and Cramer`s V were employed for statistical analysis. Ippon (27.9% of bouts) was significantly associated with Nagewaza techniques (79.8%), whereas Katamewaza (20.2%) associated with Wazari outcomes (?2 = 33.442; p < 0.001; Cramer`s V = 0.411; OR range = -2.189 to - 1.369). Subtechnical categories such as Ashi Waza and Tewaza also showed significant associations with Ippon (?2 = 38.034; gl = 6; p < 0.001; Cramer`s V = 0.438). Significant correlations with Ippon were observed in the men`s - 73 kg, - 81 kg, and - 90 kg, and in the women`s - 48 kg and - 52 kg categories. Nagewaza notably increased the likelihood of scoring Ippon, especially in these weight classes. Conversely, Katamewaza was more frequent in preliminary rounds, leading predominantly to Wazari scores. These findings suggest the importance of further examining each subcategory`s impact on scoring to develop more customised training strategies for judo athletes based on their technical strengths